Structural and thermal property changes of plasticized spinning polyacrylonitrile fibers under different spinning speeds. Issue 37 (6th June 2017) - Li, Xiang; Li, Zhaoling; Dang, Xiaonan; Luan, Dan; Wang, Feng; Chen, Hangyang; Wang, Chentao
ABSTRACT: The effect of the spinning speed on structural and thermal properties of polyacrylonitrile (PAN) fibers prepared by plasticized spinning was investigated. The PAN fibers were characterized by scanning electron microscopy, X‐ray diffraction, differential scanning calorimetry, and thermogravimetric analysis. We found that the surface morphology of the fibers was relatively smooth. The presence of a small amount of surface defects was caused by the instability of spinning process. The final fibers may have had two tensile fracture modes, that is, cluster breaking and axial split fracture. The structure of the as‐spun fibers was destroyed when the spinning speed was up to 500 m/min; this led to chain scission in the amorphous region. The final fibers exhibited mechanical properties that were roughly comparable to those of commercial PAN fibers. The changing trend in the cyclization temperature of the final fibers was consistent with that of crystallinity, which first increased and then decreased. The decomposition temperature in the amorphous region increased with increasing spinning speed. The decomposition temperature in the crystalline region increased with increasing crystallinity. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45267. Abstract :